Exploring The Barriers of Artificial Intelligence Adoption in Digital Marketing Landscape - Zahid Hussain; Iqrar Hussain Mari; Aftab Ali Rind (CV. Ulil Albab Corp, 2022)
The growing capacity of artificial intelligence (AI) has been compared to how electricity transformed our world and industries a hundred years ago. AI is changing the rules, roles and tools of marketing, as marketing is one of the most prosperous areas to implement AI in. The purpose of this paper is uncover the reasons behind the adoption of AL within the field of digital advertising. It seeks to understand the motives that drive the AL adoption and identify the potential benefits and challenges that this process may entail. The authors strive to identify the key incentives for AL adoption and observe the benefits and challenges arising from this process with the help of qualitative analysis. An analysis of interviews with 20 experts from different industries related to Marketing and AI shows that AI have impact in Marketing processes and the impact will be bigger in the future. The research questions are how to use AL in digital marketing, secondly what are the future predictions in the field of digital marketing and AI and finally what are the potential AI enabled solutions in digital marketing. The conclusions of this study indicated that companies which leverage technology in their business strategies can gain an advantage over their competitors who remain to work in traditional ways. AI can predict, analyze and personalize one to one marketing messages to consumers at scale and with precision that humans are incapable of. Companies should not fear technology but embrace it throughout the core functions of the business bearing in mind the issues around ethics and data privacy. The best time to begin gathering business data is today.